META-ANALYSIS THE EFFECT OF COMIC MEDIA TOWARD STUDENT LEARNING RESULTS AT ELEMENTARY SCHOOLS - Yurizka Nevilia; Nafiah Nafiah; Muhammad Thamrin Hidayat; Mohamad Taufiq (Universitas Negeri Medan, 2020)
Abstract: The purpose of this study was to determine the effect of comic mediatoward student learning result in elementary schools. This research method usesquantitative, the type of this reseach is meta-analysis, the data collection techniques are carried out using documentation, taking four journals that are on Google Scholar or Google Scholar. Data analysis techniques in this study used descriptive statistical analysis. The results showed 1) The learning outcomes of elementary school students who differed in place in the experimental class using comic media as learning activities increased compared to classes not using comic media in learning activities with an average grade of dick class of 51.10 and the experimental class of 65.11, 2) The use of comic media influences learning outcomes of elementary school students in different places, it can be seen from the difference in the average value between the control class and the experimental class of 14.01. Suggestions that can be given to teachers are to be creative in making use of comic media in learning activities, to the principal, to guide teachers to be creative in applying comic media in learning activities, the next researcher, impress the results of this meta-analysis study can be used as references in conducting activities further research. Keywords: comic media, student learning outcomes. Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh media komikterhadap hasil belajar siswa di Sekolah Dasar. Metode penelitian ini menggunakan kuantitatif dengan jenis penelitian meta analisis, teknik pengumpulan data dilakukan dengan cara dokumentasi, mengambil empat jurnal yang ada pada google scholar atau google cendekia. Teknik analisis data dalam penelitian ini menggunakan analisis statistik deskriptif. Hasil penelitian menunjukkan 1) Hasil belajar siswa Sekolah Dasar yang berbeda tempatnya pada kelas eksperimen yang menggunakan media komik sebagai kegiatan pembelajaran lebih meningkat dibandingkan dengan kelas yang tidak menggunakan media komik dalam kegiatan pembelajaran dengan nilai rata-rata kelas kontol sebesar 51,10 dan kelas eksperimen sebesar 65,11, 2)Penggunaan media komik memiliki pengaruh terhadap hasil belajar siswa Sekolah Dasar yang berbeda tempatnya, hal tersebut dapat dilihat dari adanya perbedaan nilai rata-rata antara kelas kontrol dan kelas eksperimen sebesar 14,01. Saran yang bisa diberikan pada guru adalah hendaklah kreatif dalam membuat menggunakan media komik dalam kegiatan pembelajaran, pada kepala sekolah, hendaklah membimbing guru agar kreatif dalam menerapkan media komik dalam kegiatan pembelajaran, peneliti selanjutnya, hedaklah hasil studi meta analisis ini dapat dijadikan rujukan dalam melakukan kegiatan penelitian selanjutnya. Kata kunci: media komik, hasil belajar siswa.